(untitled) (International Seven Journal of Health Research, 2023)
Toxic Epidermal Necrolysis (TEN) is a rare disease that was first described in 1956 by Lyell.l Its incidence is around 0.4 to 2 cases per 1 million people per year (LEWERENZ, V. et al., 2006) (DE MENDOZA-SABILLÓN et al., 2017). Although rare, it has a significant mortality rate, reaching 25% in adults. It is characterized by peeling skin, erythema, necrosis and the formation of easily dislodged blisters on both the skin and mucous membranes. Symptoms also include body aches, fever, chills, cough and keratoconjunctivitis. Lesions can also be located in the respiratory, digestive and urinary tracts, but less frequently.